Evaluating in-person and online video teaching methods to introduce landscape equipment operation and safety and responses of ornamental groundcovers and turfgrass species to drought stress - Dreiling, Levi (My University, 2025)
Universities are adapting their teaching methods to progress with changes in technology. With these shifts in teaching, educators are interested in which methods are best for certain applications. A study was conducted to determine the efficacy of online vs. traditional hands-on learning with eight types of landscape equipment: power hedge trimmer, rotary push mower, de-thatcher, overseeder, ride-on zero-turn mower, sod cutter, string trimmer, and core aerifier. Results showed that students learn landscape equipment better in-person through hands-on learning, rather than relying only on videos. The survey also showed students prefer hands-on demonstrations to become more comfortable operating these pieces of equipment. Water use in the landscape has become a more prevalent issue as the demand increases for more residential and commercial areas to be irrigated. This increase in water use indicates a need for drought tolerant plant species. We analyzed six ground cover species (Dianthus caryophyllus, Lysimachia nummularia, Phlox subulata, Sedum album, Stachys byzantina, and Vinca major) and three turfgrass species (Bouteloua dactyloides, Festuca arundinacea, and Poa pratensis) to evaluate their performance during drought and recovery. Results show S. album performed the best lasting an average of 157 d until reaching a visual quality rating of one. S. byzantina, B. dactyloides, V. major, D. Caryophyllus also performed well averaging 92, 51, 46, and 40 d, respectively, to a visual quality of one. P. subulata, P. pratensis, F. arundinacea, and L. nummularia performed the worst, averaging 35 d to decline to a visual quality rating of one. Following the dry down, the 60-d recovery period showed the following species recovered: B. dactyloides [58% Percent Green Cover (PGC)], F. arundinacea (45% PGC), L. nummularia (14% PGC), S. album (11% PGC), P. pratensis (10% PGC), and V. major (5% PGC).
Keywords: Online; In-person; Landscape equipment; Drought; Turfgrass; Groundcover